2017
DOI: 10.1038/sdata.2017.44
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a map-based reference genome sequence for barley, Hordeum vulgare L.

Abstract: Barley (Hordeum vulgare L.) is a cereal grass mainly used as animal fodder and raw material for the malting industry. The map-based reference genome sequence of barley cv. ‘Morex’ was constructed by the International Barley Genome Sequencing Consortium (IBSC) using hierarchical shotgun sequencing. Here, we report the experimental and computational procedures to (i) sequence and assemble more than 80,000 bacterial artificial chromosome (BAC) clones along the minimum tiling path of a genome-wide physical map, (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
125
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 76 publications
0
125
0
Order By: Relevance
“…In graph (d), colour‐coded dots (enlarged for better visualization) correspond to positions in which 4 cM sliding windows values exceed those thresholds. Crosses at the bottom of this graph indicate the positions of well‐known flowering time and domestication genes, according to the updated popseq map (Beier et al, ), and listed in…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In graph (d), colour‐coded dots (enlarged for better visualization) correspond to positions in which 4 cM sliding windows values exceed those thresholds. Crosses at the bottom of this graph indicate the positions of well‐known flowering time and domestication genes, according to the updated popseq map (Beier et al, ), and listed in…”
Section: Resultsmentioning
confidence: 99%
“…Markers matching unmapped contigs (chrUn) or with multiple mappings, spanning different chromosomes or more than 200 kb apart, were discarded. After quality checks, 7,479 markers (5,261 Infinium, 2,218 DArTseq) were assigned unique physical positions, and their respective genetic positions (in cM) taken from the closest marker in the POPSEQ2017 map (Beier et al, ). The genetic positions of markers SCRI_RS_224392, SCRI_RS_187102, SCRI_RS_167463, BOPA2_12_30895, and BOPA2_12_30894 were interpolated based on their physical distances.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies also showed that some LHCB members of Arabidopsis were positively involved in ABA dependent processes, such as stomatal movement, response to drought [10] and seed germination [11]. This study found that there were one to five ABREs in the promoter regions of 16 HvLHCs which indicated that expression of them may be responsive to ABA. They may also play some roles in ABA regulated pathways.…”
Section: Expression Of Hvlhcs During Barley Development and Response mentioning
confidence: 62%
“…The release of the genome of barley [16] will help us a lot in the cloning and characterization of this gene family in barley. The present study focused on extensive genome-wide …”
Section: Introductionmentioning
confidence: 99%
“…them to deduce sequence orders and to orient the assembly on the basis of the physical proximity of each sequence to others 4 . This approach was validated in work on the human genome 5 , and last year was used to construct a new genome 6 for the frog Xenopus laevis.…”
mentioning
confidence: 99%